Nilai-Nilai Nasionalisme Tokoh Eliana dalam Novel Si Anak Pemberani Karya Tere Liye - Hidayah Budi Qur'ani; Purwati Anggraini; Joko Widodo (Faculty of Languages and Arts, Universitas Negeri Padang, 2021)
Nationalism and state defense are things that are often questioned lately. This study discusses the implementation of the value of nationalism in the literary work of the novel entitled Si Anak Pemberani by Tere Liye. The method used in this study is a qualitative descriptive method. The theory used in this study is the concept of nationalism proposed by Lisyarti and Setiadi (2008). Collecting data using library techniques by reading, listening and taking notes. The results of this study indicate five forms of implementing the values of nationalism in the novel. The five forms of nationalism values include: civic nationalism, cultural nationalism, ethnic nationalism, state nationalism, religious nationalism.